0149 Nightly Sleep Characteristics are Associated with Next-Day Mindfulness. (27th May 2020) - Lee, S; Mu, C; Gonzalez, B D; Vinci, C E; Small, B J
Abstract: Introduction: Previous research shows that insufficient and poor sleep is associated with perceiving more stressors the following day. Sleep may also be associated with daily mindfulness, a state in which one is highly aware and focused on the present moment without evaluating or judging that moment. The association between high mindfulness and better sleep is well-established; yet, less is known about the temporal directionality between sleep and mindfulness. This study examined whether nightly sleep predicts next-day mindfulness, and vice versa. Methods: Participants were 60 middle-aged adults working as a full-time nurse at a cancer hospital ( M age =35.35±11.83). Using ecological momentary assessments for 14 days, we asked participants about their previous night's sleep upon waking and participants completed the 5-item state Mindful Attention Awareness Scale an average of 3 times/day. Multilevel modeling examined variance at the between- and within-person levels and tested two temporal directions simultaneously: better sleep predicting mindfulness and mindfulness predicting better sleep. Results: Daily mindfulness, sleep duration, sleep sufficiency, and sleep quality displayed 34%, 85%, 82%, and 85% within-person variation, respectively. At the within-person level, daily mindfulness was greater on days following longer than usual sleep duration ( B =0.39hrs or 23min, p <.01) and greater than usual sleep sufficiency ( B =0.26, p <.001). The within-person link between sleep sufficiency and mindfulness remained even after controlling for the strong association of workdays with less sleep sufficiency. Conversely, mindfulness was not predictive of sleep outcomes. At the between-person level, participants who had greater sleep sufficiency and higher sleep quality overall reported greater mindfulness. These associations remained after adjusting for sociodemographics, dayshift vs. nightshift, and workdays vs. non-work days. Conclusion: Sufficient sleep duration and perceived sleep sufficiency may be antecedents of how mindful individuals are the following day. Future analyses will test whether the daily link between sleep and mindfulness contributes to health outcomes. Support: This work was supported, in part, by the University of South Florida College of Behavioral & Community Sciences Internal Grant Program (PI: Lee, Grant No. 0134930).